2003
DOI: 10.1177/1052562903027003002
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Mindless Teaching Evaluations and the Moderating Effects of Image Compatibility

Abstract: Administrators use data from student evaluations of teachers (SETs) as input for making numerous decisions. However, many in the profession question the validity of SET information. This study examines the SET process from a cognitive perspective and investigates the relationship between student images of their teachers and characteristics of mindless SET completion. Questionnaire data from 127 students show significant correlations between SET scores and overall teacher evaluations, but only when images of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 39 publications
(47 reference statements)
1
34
0
1
Order By: Relevance
“…As noted earlier, evaluation is both cognitively taxing and emotionally demanding at the end of term, when students are inundated with concerns over class tests and grades. This reinforces the view that evaluation is a meaningless distraction (Dunegan and Hrivnak 2003) which has potentially serious implications in the light of MEXT (MEXT 2001) requirements that evaluation should "focus on abilities of teaching staff" with ratings from students being the sole evaluation component.…”
Section: ) the Usefulness Of Sets Feedbacksupporting
confidence: 67%
“…As noted earlier, evaluation is both cognitively taxing and emotionally demanding at the end of term, when students are inundated with concerns over class tests and grades. This reinforces the view that evaluation is a meaningless distraction (Dunegan and Hrivnak 2003) which has potentially serious implications in the light of MEXT (MEXT 2001) requirements that evaluation should "focus on abilities of teaching staff" with ratings from students being the sole evaluation component.…”
Section: ) the Usefulness Of Sets Feedbacksupporting
confidence: 67%
“…Another is the students' desire to send a message. Dunegan and Hrivnak (2003) reported that when students found an instructor whom they did not like, they carefully completed the evaluation so that their perception of overall performance and SET were correlated, but if the instructor aligned with the students' ideal, the association between performance and the SET was not significant. In other words, under this condition, the students simply and "mindlessly" (the authors' term) marked the form.…”
Section: Review Of the Literature The Halo Effectmentioning
confidence: 99%
“…This finding is consistent with literature presented, suggesting that the current cohort of students would not benefit from end of module or end of degree evaluations (Becker and Watts 1999;Davis 2009). No respondent indicated concerns raised in the literature such as the students did not take them seriously (Dunegan and Hrivnak 2003). There was, however, one Chinese student who suggested that there was concern about how valid responses on summative evaluations are: 'because we always evaluate the lecture after the exams, maybe there are more emotions'.…”
Section: Resultsmentioning
confidence: 99%
“…There is also the concern that students do not take SETs seriously and see them as a chore (Dunegan and Hrivnak 2003). Another criticism is that SETs may discourage faculty from challenging students too much, should they be punished at the end of the semester through the SETs (Parayitam, Desai, and Phelps 2007).…”
Section: Criticisms Of Setsmentioning
confidence: 96%
See 1 more Smart Citation